UPAYA REFRESIF POLSEK TURIKALE KABUPATEN MAROS DALAM MENANGGULANGI TINDAK PIDANA PERJUDIAN - Zulfadli, Zulfadli (Institut Agama Islam Negeri Fattahul Muluk Papua, 2022)
In accordance with article 303 of the Criminal Code and Law no. 7 of 1974 concerning Control of Gambling This research was initiated with the intention of examining the repressive efforts carried out by the Turikale Resort Police in Maros Regency to eradicate gambling as a crime. Empirical legal research is used in this study. types of research. Primary and secondary legal materials are used as a source of research data. By managing primary data obtained from Polres Turikale Maros Regency, this research is included in the type of qualitative data. This study found that people in the Turikale Law Area of ​​the Polsek in Maros Regency gambled in various ways, including cockfighting and card gambling (Domino and Remi). In addition, there are several factors that motivate people to gamble, including environmental factors, environmental factors, and environmental factors. Perception of skills, perception of the possibility of winning, and the low level of public education. The Turikale Police have taken the following steps to combat gambling offences: Repressive measures are taken after the crime has occurred, whereas preventive measures are taken at the preventive level.